Determinan dan Trend Kemiskinan di Kabupaten Wonosobo Provinsi Jawa Tengah - Farida Nur Isnaini; Abdul Aziz Ahmad; Suharno Suharno (Universitas Batanghari Jambi, 2020)
This study aims to analyze the effect of population, education, regional Minimum Wages, inflation, and Gross Regional Domestic Product on poverty and analyze poverty trends in Wonosobo Regency. This study uses secondary data in the form of time series data with an observation period of 2002-2017 and the research method is multiple linear regression with the Ordinary Least Square model. The analysis shows that education, regional minimum wages and gross regional domestic product have a negative and significant impact on poverty in Wonosobo Regency. Population growth, and inflation does not have a significant effect on poverty in Wonosobo Regency. In addition, the future poverty trend of Wonosobo Regency is negative. These findings imply the first need for skills and expertise training programs in improving the quality of education. Second, the government must increase regional minimum wages, so that people can meet their daily needs. The government needs to increase economic growth in all sectors of the economy by using its potential.